PENGARUH STRATEGI PROMOSI DIGITAL, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA UMKM SEKTOR MAKANAN DAN MINUMAN DI KOTA KENDARI - Dzulfikri Azis Muthalib; Isalman (STIE ENAM ENAM KENDARI, 2025)
This study aims to analyze the effect of digital promotion strategy, brand image, and product quality on consumer purchasing decisions of micro, small, and medium enterprises (MSMEs) in the food and beverage sector in Kendari City. This research employed a quantitative approach using a survey method. The population of this study consisted of all food and beverage MSMEs in Kendari City, which is infinite in nature. Therefore, the sample size was determined using the Lemeshow formula with a 95% confidence level and a 10% margin of error, resulting in 96 respondents. The sampling technique used was accidental sampling. Data were collected through questionnaires that had been tested for validity and reliability. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that digital promotion strategy, brand image, and product quality partially have a positive and significant effect on consumer purchasing decisions. Furthermore, the simultaneous test shows that these three independent variables collectively have a positive and significant effect on purchasing decisions of consumers in the food and beverage MSME sector in Kendari City. These findings suggest that optimizing digital promotion strategies, strengthening brand image, and maintaining high product quality are essential factors in encouraging consumer purchasing decisions and enhancing the competitiveness of MSMEs in the digital era.